A Companion to film theory - Miller, Toby; Stam, Robert, 1941- (Blackwell companions in cultural studies, 1999)
This volume of specially commissioned work by experts in the field of film studies provides a comprehensive overview of the field. Its international and interdisciplinary approach will have a broad appeal to those interested in this multifaceted subject. This major film theory collection:* Represents material under a variety of headings, including class, race, gender, queer theory, nation, stars, ethnography, authorship, and spectatorship* Offers an international approach to the subject, including coverage of topics such as genre, image, sound, editing, postmodernism, culture industries, early.